Confronting the death penalty: how language influences jurors in capital cases - Conley, Robin (Oxford studies in language and law, 2016)
Introduction : that's the hardest thing I've ever had to do -- Doing death in Texas : studying jurors in the death penalty state -- I hope I'm strong enough to follow the law : emotion and objectivity in capital jurors' decisions -- Facing death : empathy, emotion, and embodied actions in jurors' decisions -- Linguistic distance and the dehumanization of capital defendants -- Agents of the state : Capital jurors' accountability for death sentences -- Conclusions : linguistic dehumanization and democracy